2022
DOI: 10.4251/wjgo.v14.i10.1981
|View full text |Cite
|
Sign up to set email alerts
|

Cuproptosis-related long non-coding RNAs model that effectively predicts prognosis in hepatocellular carcinoma

Abstract: BACKGROUND Cuproptosis has recently been considered a novel form of programmed cell death. To date, long-chain non-coding RNAs (lncRNAs) crucial to the regulation of this process remain unelucidated. AIM To identify lncRNAs linked to cuproptosis in order to estimate patients' prognoses for hepatocellular carcinoma (HCC). METHODS Using RNA sequence data from The Cancer Genome Atlas Live Hepatocellular Carcinoma (TCGA-LIHC), a co-expression net… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…microRNA (miRNAs) and lncRNAs have recently gained attention as possible markers for prediction of HCC and therapy outcome. In the last two years, many studies have been published on this topic [ 136 , 137 , 138 , 139 , 140 ]. One of them set up a prediction model based on eight lncRNAs strongly associated with TMB and tumor immune infiltration to predict HCC patients’ prognosis [ 141 ].…”
Section: Combination Of Tmb and Other Specific Genetic Biomarkersmentioning
confidence: 99%
“…microRNA (miRNAs) and lncRNAs have recently gained attention as possible markers for prediction of HCC and therapy outcome. In the last two years, many studies have been published on this topic [ 136 , 137 , 138 , 139 , 140 ]. One of them set up a prediction model based on eight lncRNAs strongly associated with TMB and tumor immune infiltration to predict HCC patients’ prognosis [ 141 ].…”
Section: Combination Of Tmb and Other Specific Genetic Biomarkersmentioning
confidence: 99%
“…Chen et al [16].also reported that cuproptosis-related LncRNA signature with AUC of 0.719, 0.695, and 0.638 at 1-, 3-5-year. While the highest AUC was 0.741 in the study by Huang [17]. In our study, the highest AUC is 0.800, which indicates this DECRLs signature has strong predictive power.…”
Section: Discussionmentioning
confidence: 40%
“…Our results elucidate the multi-omics characteristics of cuproptosis related genes in pan-cancer, establish a CPI index model that predicts the prognosis of CRC patients and evaluates the correlation between CuRGs and immune infiltration levels. In recent cuproptosis related studies, Huang et al proposed a risk model for cuproptosis related lncRNAs to predict the prognosis of hepatocellular carcinoma patients [ 23 ]. Xu et al developed a strategy to induce copper poisoning using copper-based nanomaterials to treat cancer [ 24 ].…”
Section: Discussionmentioning
confidence: 99%